Attributes of narrative game aesthetics for perceived cultural learning - Abdul Syafiq, Bahrin (2017)
Previous researches are mostly concerned on non-holistic game aesthetics for learning in various interactive media platforms. There is lack of studies on attributes of narrative games aesthetics which may contribute to perceived cultural learning. Therefore, this study aims to propose a conceptual model of narrative game aesthetics for perceived cultural learning. Three specific objectives were formulated: (i) to determine game aesthetics that contribute to perceived cultural learning in narrative games, (ii) to develop a narrative game based on the determined game aesthetics, and (iii) to produce empirical evidence on the contribution of game aesthetics towards perceived cultural learning. The research methodology comprises of three main phases: conceptual model development, prototype development, and user evaluation. For the first phase, the conceptual model was developed based on previous literature and reviewed by six experts. In the second phase, prototype development was then developed according to the conceptual model. Finally, user evaluation was employed using quasi experiment which involved 43 participants. Data analysis is conducted using descriptive analysis, correlation analysis, and observation. Findings indicate that six out of 10 attributes namely image and graphic; layout; shape and form; texture; voice; and music, are significantly correlated to perceived cultural learning. The observation results also indicate that these attributes can amplify game experience for perceived cultural learning. In a nutshell, this study has identified attributes of narrative game aesthetics for perceived cultural learning. It further provides empirical evidence on contributions of these attributes of narrative game aesthetics to perceived cultural learning. The outcome of this study will provide guidelines for narrative game designers and developers whom interested to inculcate cultural learning in their games